Practical interventions for young people at risk - Geldard, Kathryn, (Sage, 2009)
'The book's rich, relevant and comprehensive contributions from experienced writers make it a substantial resource for teaching, reference and research' - Mark Prever, trainer, writer and supervisor. 'The needs and problems of young people are currently extremely topical and justify a dedicated textbook. The wide range of internationally renowned authors contributes to the strengths and diversity of this publication, enhancing its potential as a resource for students and professionals' - Jenny Pinfield, University of Worcester. This book responds to the urgent need for practical intervention approaches targeting young people at risk. It provides a much needed practical resource for practitioners and students from a variety of helping professions. Focussing on interventions that practitioners can use in collaboration with the young person, the book offers hands-on strategies for addressing challenges and issues typically faced by young people, such as: depression, suicide and self-harm; substance misuse; problematic sexual behaviour; marginalised youth; and, mental health issues. Throughout the book, multi-disciplinary and international authors share their expertise, highlighting relevant evidence-based interventions and considering themes such as anti-oppressive practice, culture, values and ethics. It will prove invaluable reading for students and practitioners working with young people, especially in the fields of youth work, social work, psychology, counselling, and education.